Indole-based allosteric inhibitors of HIV-1 integrase. Issue 19 (1st October 2016) - Patel, Pratiq A.; Kvaratskhelia, Nina; Mansour, Yara; Antwi, Janet; Feng, Lei; Koneru, Pratibha; Kobe, Mathew J.; Jena, Nivedita; Shi, Guqin; Mohamed, Mosaad S.; Li, Chenglong; Kessl, Jacques J.; et al.
Graphical abstract: Abstract: Employing a scaffold hopping approach, a series of allosteric HIV-1 integrase (IN) inhibitors (ALLINIs) have been synthesized based on an indole scaffold. These compounds incorporate the key elements utilized in quinoline-based ALLINIs for binding to the IN dimer interface at the principal LEDGF/p75 binding pocket. The most potent of these compounds displayed good activity in the LEDGF/p75 dependent integration assay (IC50  = 4.5 μM) and, as predicted based on the geometry of the five- versus six-membered ring, retained activity against the A128T IN mutant that confers resistance to many quinoline-based ALLINIs.